It is possible for people diagnosed with schizophrenia to recover - Valinejad, Carol; Smith, Jan (Groupwork, 2012)
Services that support individuals with a diagnosis of Serious Mental Illness are called upon to deliver services that seek to promote their recovery.The National Institute for Mental Health in England (NIMHE, 2005), have been working towards defining the key features of what a recovery oriented service should look like. Optimistic as it may seem, services are a long way to undoing the effects of institutionalisation in the lives of many service users. This article provides an account of an evaluation of a Recovery Group designed to introduce participants to the recovery paradigm, in an attempt to help enhance their hopefulness about their future. It was hypothesised that when people are hopeful about achieving their goals, then they will become more motivated to pursue meaningful activities. An eight week group was conducted using outcome measures such as the Beck Hopelessness scale (1974), Lancashire Quality of Life scale, Bradburn Affect Scale and Cantill’s Life Ladder. Seven mental health service users from a Rehabilitation Inpatient Unit, and Community Team participated in the Recovery group, of whom four service users completed the programme. Despite methodological limitations of this evaluation some improvements were noted for the service users in terms of improved quality of life, a sense of optimism for the future and improved psychological well-being.